Perancangan Sistem Informasi Registrasi Pasien BPJS Bayi Baru Lahir Guna Menunjang Efektifitas Pelayanan Pasien - Salimah, Nuroh; Syahidin, Yuda; Elvira, Shinta (Program Studi Teknik Informatika Universitas Pamulang, 2024)
BPJS participants are people who have registered as BPJS members, including newborns. For newborns who have not been registered as BPJS participants, they can be registered with the BPJS or in every hospital that serves BPJS registration for newborns a maximum of 28 days after the baby's birth. Researchers use a qualitative descriptive approach method that aims to explain certain conditions that are focused on understanding a problem objectively. In this method, researchers and system users must work together in order to obtain the research subject as the final result. The data collection technique used in this research is the primary data collection method, namely interviews between researchers and medical staff, especially in the BPJS registration section so that researchers get accurate results. The development method used in the design process is SDLC (System Development Life Cycle) with the waterfall method. SDLC defines the models and procedures used in the development of software systems and also shows how researchers make the transition from identification to solution implementation. Based on the results of the research, there are problems found, namely the server used sometimes experiences several problems such as many bugs because the server used by the hospital is still combined with other health services. The BPJS patient registration information system for newborns owned by this hospital can help and simplify the problem if the central server used is experiencing problems.